DEBTORS LEGAL CERTAINTY POST CONSTITUTIONAL COURT’S DECISSION NO 18/PUU-XVII/2019 CONCERNING PARATE EXECUTION FOR FIDUCIARY GUARANTEE OBJECTS - Satya M, Bhatara Eri; Winanti, Atik (LPPM STIH Putri Maharaja, 2023)
After the publication of PMK No. 18/PUU-XVII/2019, it essentially canceled the parate execution for the object of fiduciary guarantees over the debtor's control. However, until now, parate executions are still being carried out to resolve disputes between debtors and creditors. This research aims to examine the legal certainty of debtors and the legal consequences of PMK Decision No. 18/PUU-XVII/2019 in cases of partial execution of fiduciary collateral objects. This research method is normative law with a statutory approach, and the main data is secondary data. The results of this research: the legal protection given to debtors if the execution process continues after PMK No. 18/PUU-XVII/2019 can take legal action as an appeal as a stance to oppose the court's decision on a judge's decision which is deemed not to provide justice. The debtor can also take criminal legal action if the execution is still carried out using coercion because he has fulfilled the criminal offense. The impact of PMK Law No. 18/PUU-XVII/2019 on the legal certainty of debtors in cases of parate execution, the object of the fiduciary guarantee is to conditionally cancel the parate execution. However, many execution parate cases after the publication of PMK No. 18/PUU-XVII/2019 indicates that there is no legal protection for debtors as well as legal certainty regarding the application of the execution parate regulations. This further reduces the debtor's legal certainty because the judge's view of the two cases of execution parate for the object of fiduciary collateral did not consider execution parate as an unlawful act.